2011
DOI: 10.1021/bm201111d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polymer Architecture and Molecular Weight of Poly(2-(dimethylamino)ethyl methacrylate) Polycations on Transfection Efficiency and Cell Viability in Gene Delivery

Abstract: Nonviral gene delivery with the help of polycations has raised considerable interest in the scientific community over the past decades. Herein, we present a systematic study on the influence of the molecular weight and architecture of poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) on the transfection efficiency and the cytotoxicity in CHO-K1 cells. A library of well-defined homopolymers with a linear and star-shaped topology (3- and 5-arm stars) was synthesized via atom transfer radical polymerization (AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
155
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(163 citation statements)
references
References 63 publications
6
155
2
Order By: Relevance
“…[3][4][5][6][7] Often carriers with cationic net charge interact strongly with and are capable of penetrating the cellular membrane, leading to high delivery efficiencies but this is often accompanied by impaired cell viability and clearance by the reticuloendothelial system. 8,9 An interesting class of nanocarriers is block copolymer micelles with diameters below 50 nm as these are reported to deeply penetrate tumor tissue in spite of elevated interstitial pressure. 10 In addition, PEGylation generally facilitates long circulation times while, ideally, a surface-tag might induce specific interaction of the particle with the targeted cells or tissues.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Often carriers with cationic net charge interact strongly with and are capable of penetrating the cellular membrane, leading to high delivery efficiencies but this is often accompanied by impaired cell viability and clearance by the reticuloendothelial system. 8,9 An interesting class of nanocarriers is block copolymer micelles with diameters below 50 nm as these are reported to deeply penetrate tumor tissue in spite of elevated interstitial pressure. 10 In addition, PEGylation generally facilitates long circulation times while, ideally, a surface-tag might induce specific interaction of the particle with the targeted cells or tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Polyplexes with H(S)-7.9 at an N/P ratio of 10 also showed almost no cytotoxicity, while those at an N/P ratio of 20 had some cytotoxicity, but not significant. Previous studies have reported that poylcations with higher M w , such as PEI [40] and poly(2-(dimethylamino)ethyl methacrylate) (PDMAEMA) [41], show more cytotoxicity than those with lower M w . In our study, H(S)-7.9 with the largest M w at an N/P ratio of 20 showed a slight cytotoxicity toward cells.…”
Section: Cytotoxicity Of Lpei-peptide Conjugatesmentioning
confidence: 99%
“…For instance, non-linear polymers appear to be more efficient and less cytotoxic than linear polymers of the same size [6,13,14]. Recently, our group has published first data showing that star-shaped nano-structures with many arms extending from a central core may result in non-viral polycationic transfection agents with the ability to transfect cells, which up to then had been considered unsuitable targets for non-viral gene delivery [15].…”
Section: Introductionmentioning
confidence: 99%